Dust exposure in coeliac disease: a case-referent study. Issue 10 (October 1991) - Axmacher, B; Axelson, O; Frödin, T; Gotthard, R; Hed, J; Molin, L; Brage, H N; Ström, M
Abstract : Case series of coeliac disease show that chronic allergic alveolitis (farmers' lung) and fever reactions due to exposure to organic dust (organic dust toxic syndrome) commonly occur among subjects with coeliac disease and dermatitis herpetiformis, these being related disorders. In this case-referent study 105 cases of coeliac disease and dermatitis herpetiformis were compared with 237 referents from the general population by means of a mail inquiry regarding exposure to various environmental factors. Increased odds ratios were obtained with exposure to various farm animals and more clearly for cotton dust, although numbers were few. Animal husbandry in Sweden invariably means heavy exposure to organic dust. The fact that comparatively few persons reported dust exposure may be of doubtful validity in view of the high frequency of exposure to farm animals reported by the cases.